2023
DOI: 10.3390/foods12173224
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Stability of a Novel Toxin in Scallop Mantle Tissue

Nabuki Maeda,
Takahiro Yumoto,
Geng Xiong
et al.

Abstract: Previous studies have shown that mice fed a diet containing 1% mantle tissue exhibited decreased food consumption and led to death. Toxic substances present in the mantle tissue have been isolated and identified. In the present study, we explored the characteristics and stability of mantle tissue toxicity. The treatment of mantle tissue with 1 mM hydrochloric acid, 1 mM sodium hydroxide, 1 mM dithiothreitol, and 1 mM hydrogen peroxide followed by heating did not significantly reduce the toxicity of mantle tiss… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Real-time polymerase chain reaction analysis showed that the uptake of mantle tissue caused changes in the small intestine’s inflammation and endoplasmic reticulum stress markers. These outcomes indicate that scallop mantle feeding leads to toxicity after initial damage to the small intestinal tissue [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Real-time polymerase chain reaction analysis showed that the uptake of mantle tissue caused changes in the small intestine’s inflammation and endoplasmic reticulum stress markers. These outcomes indicate that scallop mantle feeding leads to toxicity after initial damage to the small intestinal tissue [ 8 ].…”
Section: Introductionmentioning
confidence: 99%